COLLABORATION STRATEGY IN THE PENTA-HELIX CONCEPT: DERADICALIZATION PROGRAM FOR TERRORIST SEPARATISM GROUPS IN PAPUA - Firmansyah, Muhammad Zaenuddin; Priyanto, Sapto; Bilney, Megan (UI Scholars Hub, 2022)
Abstract On 29 April, 2021, The Indonesian Government declared the Armed Criminal Group (KKB) as a Separatism Terrorist Group (KST), in response to the casualties, both from the military and civilian parties. In particular, the death of the Kabinda of Papua and Bharada Komang was a catalyst for this announcement as previous conflict resolution steps failed to address the ongoing conflict in Papua. The increased risk of terrorism in the Papuan region is driven by the lack of research into focused deradicalization programs. In this article, the author seeks to address how a targeted deradicalization program is an appropriate conflict approach to this situation. This paper proposes the Penta-Helix concept as a suitable program, which seeks to facilitate the specific needs for deradicalisation in this region. The Penta-Helix concept is based on five factors: the history of separatism in Papua, the traditions of the Papuan people, the variance between religious and secular radicalism, the concept of deradicalisation and disengagement, and the TNI-Polri Operasi Penggalangan and the current deradicalization program in Indonesia. The collaboration and cooperation of the Pentahelix concept’s five factors, in the form of representative actors, are essential in the development and implementation of three stages of the proposed deradicalization program: identification, psychological adjustment, and aftercare. Finally, this paper outlines eight recommendations, called the “Optimization Strategy for the Deradicalization Program”, which intend to be applied for sustainable deradicalisation of Papuan terrorism separatists.